2016
DOI: 10.1016/j.cemconcomp.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silica fume content on microstructure development and bond to steel fiber in ultra-high strength cement-based materials (UHSC)

Abstract: The use of silica fume can significantly enhance mechanical properties of concrete given its beneficial filling and pozzolanic effects. In this study, a simple and effective double-side pullout testing method was adopted to characterize the interfacial bond properties, which include pullout load-slip relationship, bond strength, and pullout energy, of steel fiber-matrix in ultra-high strength cement-based material (UHSC) with 0-25% silica fume by the mass of binder. The effects of silica fume content on flowab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(93 citation statements)
references
References 38 publications
6
85
0
2
Order By: Relevance
“…3,4 Recently, the use of nanoparticles in cementitious materials to improve their mechanical properties by controlling nanoscale crack formation has received widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, the use of nanoparticles in cementitious materials to improve their mechanical properties by controlling nanoscale crack formation has received widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…The pore range of this peak (5-50 μm) is related to preexisting microcracks and entrained or entrapped air [45]. These pores, which did not change with curing ages, were possibly formed with the change of rheology of the mortar by SF addition [46]. As can be seen in Figure 6 that compares cumulative pore volumes of three samples at 28 days, the extra SF (over 7.5 wt %) is expected to play a role as a filler.…”
Section: Porosity Analysismentioning
confidence: 99%
“…This indicates that the volume of mesopores (4.5-25 nm) of SF_15 were increased due to expansion with curing age. It has been reported that the pores finer than 10 nm mainly affect shrinkage and creep of hardened cementitious materials [46], and also the degree of capillary tension and stress for drying shrinkage is increased with a finer pore system (below 80 nm range in pore diameter) [15,48]. Thus, this distinct expansion might be attributed to the accelerated drying shrinkage of matrix and resultant micro cracks, as shown in the low W/B (0.25) cement paste with SF (20% of cement) [49].…”
Section: Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies show that these inclusions not only improve the packing of particles but also produce crack bridging phenomena by densifying the nanostructures [18,27]. Nano particles control the C-S-H reaction and improves the concrete durability [28][29][30][31][32][33]. Among above mentioned nano materials, MWCNTs possess unique and exceptional characteristics in terms of physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%